2015
DOI: 10.3233/jad-150035
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the 5′-AMP-Activated Protein Kinase in the Cerebral Cortex of Young Senescence-Accelerated P8 Mice and Association with GSK3β- and PP2A-Dependent Inhibition of p-tau396 Expression

Abstract: The 5'-AMP-activated protein kinase (AMPK), which is a sensor of cellular energy, regulates neuronal survival and energy homeostasis. However, the roles of AMPK in the pathogenesis of Alzheimer's disease (AD) are unclear. The senescence-accelerated mouse prone 8 (SAMP8) strain is characterized by deficits in learning and memory, exhibits pathological characteristics of AD as early as 5 months of age, and is being increasingly recognized as a model of AD. Here, we investigated the relationship between AMPK acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…This hypothesis was supported by evidence that the pattern of p-AMPK in the cortex of SAMP8 at 2, 5 and 10 months of age was correlated with the levels of p-GSK3β S9 and negatively correlated with the levels of p-tau S396. Moreover, a previous study of the authors indicated that 5-aminoimidazole-4-carboxamide ribonucleotide-induced AMPK activation reduces GSK3β activity and levels of p-tau S396 in differentiated SH-SY5Y cells (27). Thus, these data suggested that the activity of AMPK in the cerebral cortex of young SAMP8 was associated with decreased levels of p-tau S396 via a reduction of GSK3β activity.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This hypothesis was supported by evidence that the pattern of p-AMPK in the cortex of SAMP8 at 2, 5 and 10 months of age was correlated with the levels of p-GSK3β S9 and negatively correlated with the levels of p-tau S396. Moreover, a previous study of the authors indicated that 5-aminoimidazole-4-carboxamide ribonucleotide-induced AMPK activation reduces GSK3β activity and levels of p-tau S396 in differentiated SH-SY5Y cells (27). Thus, these data suggested that the activity of AMPK in the cerebral cortex of young SAMP8 was associated with decreased levels of p-tau S396 via a reduction of GSK3β activity.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, inhibited activity of AKT and expression of glucose transporter 4 in the skeletal muscle in the SAMP8 strain, when compared to the SAMR1 control strain, has been reported (26). In a previous SAMP8 study of the authors, there was observation of AMPK activity upregulation in the cortex of young SAMP8 (pre-symptomatic age), when compared with SAMR1 mice; a change attributable to the inhibition of tau phosphorylation at Ser396 (27). However, the chronological relationship between metabolic regulators and AD pathogenesis, particularly in tau hyper-phosphorylation in SAMP8, has not been fully elucidated.…”
Section: Chronological Changes In the Expression Of Phosphorylated Tamentioning
confidence: 89%
“…Phosphorylation at this site is mediated by different kinases, but it is reported that GSK3β is the major tau kinase [103]. In addition, the level of hyperphosphorylation is regulated by the balance between phosphorylation by the different kinases and activity of dephosphorylating enzymes phosphatases mainly protein phosphatases 2A (PP2A) [104].…”
Section: Ampk and Tauopathymentioning
confidence: 99%
“…Activated AMPK is abnormally accumulated in tangle-and pre-tangle-bearing neurons in AD patients and other tauopathies (Vingtdeux et al 2011). AMPK activation has been shown to influence tau phosphorylation at Ser 262 , Ser 356 and Ser 396 (Yoshida and Goedert 2012;Thornton et al 2011;Lee et al 2013;Kim et al 2015) and Ab production (Vingtdeux et al 2010;Won et al 2010;Chen et al 2009), although the results were conflicting.…”
Section: Introductionmentioning
confidence: 97%